(untitled) - H Douglas Brown (Englewood Cliffs, New Jersey, 1994)
The book synthesizes the accumulation of knowledge into a practical principles approach to teaching English as a second or foreign language. It consist of three parts: *) Part One: Foundations for classroom practice. *) Part Two: Contexts of teaching. *) Part Three: Designing anf implementing techniques
Keywords: english language - study and teaching - foreign speakers,interaction analysis in education,language and languages - study and teaching